Comparison of Efficiency of Floating Breakwater and Rubble Mound Breakwater - พลอยประดับ ปณพงศ์; ฤทธิ์พริ้ง สมปรารถนา (Engineering and Technology Horizons, 2019)
This study aims to design floating breakwater model and the rubble mound breakwater model. The two types of breakwater model were investigated to compare the efficiency. Moreover, the influence of waves at different wave height which affected to the changing of wave characteristics was examined as well. The floating breakwater was designed in three types of structures: the bioball 1, the bioball 2 (with filter mat) and the foam. Wave transmission coefficient (Ct) of three types floating breakwaters were determined in wave basin at 25, 27.5 and 30 cm of the water depth with 0.025-0.048 of wave steepness. Moreover, the foam floating breakwater was investigated at drowning level 50% and 80%. The results in the floating type found the Ct of the foam floating breakwater at drowning level 80% were 0.58-0.97which represented the highest efficiency for reducing Ct. The result of comparison between the rubble mound breakwater and the foam drowning level 80% was found that the rubble mound breakwater could reduce Ct better (0.35-0.66) because the porosity and the ratio of drowning level could be affected to Ct. However, Ct from the breakwater were found similarly in some wave steepness.